Surgical residents’ challenges with the acquisition of surgical skills in operating rooms: A qualitative study - LEILA SADATI; SHAHRAM YAZDANI; PEIGHAM HEIDARPOOR (Journal of Advances in Medical Education and Professionalism, 2021)
Introduction: Training in operating rooms is challenging. Specifically, surgical residents often experience a stressful environment in training arenas that, in turn, might affect their ability in the acquisition of the required qualifications. This study aims at the qualitative explanation of how the surgical residents acquire the surgical skills in operating rooms.Methods: This qualitative study was conducted in 2019-2020 using the conventional content analysis method. Participants were selected using purposive sampling. Data were collected through 25 semi-structured in-depth interviews. Then, the interview transcriptions were analyzed in MaxQDA2 software using the content analysis method.Results: The data were classified into two main categories, namely challenges/obstacles and strategies for dealing with the challenges. The data in the first category were further classifiedinto four subcategories, including burnout, confusion in technique selection, unequal learning opportunities, ignorance, and responsibility misassignment. Similarly, four subcategories of establishing communication channels with chief residents and faculty members, learning by the non-surgeon pathway, covert progress in the learning path, and taking advantage of force from a position of power in the learning path were considered for the second category.Conclusion: Based on the findings of the study, surgical residents face serious challenges and obstacles in their training course. To address these challenges, the curriculum of the surgical course needs to be improved with the emphasis on the balanced responsibility assignment and enhanced human communication.